The effect of small group simulation-based interprofessional education on non-technical skills of anesthesia providers: A randomized controlled trial. - Khalafi, Ali; Sarmeydani, Nooshin Sarvi; Albooghobeish, Masoumeh; Saidkhani, Vahid; Adarvishi, Sara (Nursing & Midwifery Studies, 2024)
Background: Most serious adverse events in health care are related to non-technical skills failures. Anesthesiology profession, due to its vital, risky and decisive nature, is more focused on technical, physiological and medicinal aspects compared with other professions, and anesthesia experts and researchers have not paid serious attention to non-technical aspects of their work. Objectives: This study examined the effect of simulation-based interprofessional education (SBIPE) in small groups on non-technical skills of anesthesiologists and nurse anesthetists. Methods: This single-blind randomized controlled trial was conducted during April and May 2023 on anesthesiologists and nurse anesthetists in the operating room of Imam Khomeini Hospital, Ahvaz, Iran. Participants included 64 anesthesiologists and nurse anesthetists who were randomly assigned into an intervention group (n=32) and a control group (n=32). The intervention group was divided into small groups to receive three hours of SBIPE. The Anesthetists' Non-Technical Skills (ANTS) scale which encompasses four components of task management, team working, situation awareness, and decision-making was used to collect data. To analyze the data, independent and paired t-tests were used. Results: In the intervention group, the mean scores of task management, team working, situation awareness and decision-making were 9.32±2.29, 7.96±2.05, 7.84±1.91 and 6.00±1.61 at baseline and increased to 12.36±2.18, 12.28±2.31, 12.28±2.19 and 10.04±1.62, respectively (P<0.001). In the control group, however, changes were significant only in the task management component (9.20±2.27 to 10.76±1.59) (P=0.004). Conclusion: Compared with simulation-based uniprofessional education, SBIPE was more effective in improving non-technical skills of anesthesia providers. Therefore, similar interprofessional education programs can be used to improve non-technical skills of anesthesiologists and nurse anesthetists.